Peningkatan keterampilan menulis narasi melalui model pembelajaran kooperatif tipe concept sentence menggunakan media gambar seri kelas III sekolah dasar - Yuliani, Wahyu Dwi; Mahfud, Hasan; Sriyanto, Muhammad Ismail; Supardiyono, Supardiyono (Didaktika Dwija Indria, 2019)
The aim of this research was to improve the narrative writing skill through Cooperative learning model of Concept Sentence type with picture series media in third grade students of State Primary School of Kebonsari Kebumen in the academic year 2018/2019. This research was a Classroom Action Research (CAR) with a cycles model. This research  was carried out in two cycles. The subjects of this reseach were the teacher and students of 3rd grade in Kebonsari, Kebumen state primary school. The data collection techniques in  this research  include observation, interview, test, and document. The data validity test of this research were source and technique triangulation and content validity. The data analysis techniques of this research were interactive model of analysis and descriptive comparative technique. The average value of the narrative writing skills at pre-action stage reached 63,20 with 32,35% classical completeness or as much as 11 out of 34 students succeeded. Then in cycle I the average value of narrative writing skills achieved 75,08 with 70,59% of classical completeness or about 24 out of 34 students succeeded and increased again up to 81,06 with 88,23% of classical completeness or about 30 out of 34 student succeeded in cycles II.     Keywords: narrative writing skills, Concept Sentence model, picture series